Risk Research on Blockchain Technology in Interactive Mobile Hospitals Based on the Entropy Method - Zhang, Cui; Wang, Xiaofeng; Juraev, Davron Aslonqulovich; Efendiev, Rakib Feyruz; Yue, Xiao-Guang (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This paper aims to study the risk situation of blockchain technology in interactive mobile hospitals. With the development of blockchain technology, interactive mobile hospitals have begun to use blockchain technology to empower technological capabilities in aspects such as diagnosis and treatment management, data security, and sharing. Firstly, by referring to relevant literature, this paper identifies that the existing risks include technical risks, privacy risks, compliance risks, management and operation risks, as well as cognitive and acceptance risks. Then, the entropy method is used to analyze the weights of these risks, and the fuzzy comprehensive evaluation (FCE) method is applied to calculate the risk levels. The calculation results show that the overall risk score of blockchain technology in interactive mobile hospitals is 63.3705, among which the technical risk score is 59.3491, the management and operation risk score is 59.8643, the privacy risk score is 65.8097, the compliance risk score is 64.1854, and the cognitive and acceptance risk score is 69.2427. This study conclusion is that the degree of risk of blockchain technology in interactive mobile hospitals is between general and high. Among them, technical risks and management and operation risks are between low and general, while privacy risks, compliance risks, and cognitive and acceptance risks are between general and high. Finally, this paper puts forward corresponding countermeasures and suggestions based on the risk conclusions. This paper hopes that the interactive mobile hospital industry can strengthen risk management in aspects such as enhancing technological research and development, protecting privacy, improving laws and regulations, optimizing management processes, and increasing the awareness of all parties so as to promote the healthy and stable development of the entire mobile medical industry.